Appraising legal measures against bid rigging in Malaysia / Mohd Safri Mohammed Na’aim, Anida Mahmood, Jusniza Abd Jamal, Cartaz Ummu Syawaeda Jaiman and Nurulhasni Shaari @ Mat Saman - Mohammed Na’aim, Mohd Safri; Mahmood, Anida; Abd Jamal, Jusniza; Jaiman, Cartaz Ummu Syawaeda; Shaari @ Mat Saman, Nurulhasni (UiTM Cawangan Johor, 2023)
Bid rigging is an agreement between bidders that may prevent or restrict competition in tendering activities. It has negative consequences for the economy and customers' well-being. In realising its harmful effects, bid rigging is prohibited under the Competition Act 2010 (Act 713)(CA 2010). Under the CA 2010, the Malaysia Competition Commission (IVfyCC) has investigated more than 3,000 companies for rigging tenders worth RM5.8billion. This shows that bid rigging is prevalent and, if not addressed properly, can have a negative impact on the country's economy. The question arises as to what other legal measures are being implemented in Malaysia to prevent bid rigging apart from the CA 2010. This research adopts a doctrinal approach involving a detailed analysis of the relevant legal provisions, legal documents and scholarly writing related to this area. The research found that through the examination of literatures, in addition to the CA 2010, there are other legal measures relevant to bid rigging in Malaysia. Firstly, the Anti-Corruption Commission Act 2009 (Act 694) (ACCA 2009) that can be used against bid rigging if it involves bribery. Besides, matters relating to bid rigging in government procurement are subject to rules as mentioned in the followings: (i) Treasury Instructions, (ii) Malaysian Treasury Circular - Integrity in Government Procurement (PK 1.6), (iii) Malaysian Treasury Circular - Disciplinary Action against Companies in Government Procurement (PK 8) and (iv) Integrity Pact in Government Procurement. Keywords: Bid rigging, Competition, Competition Act 2010, Malaysia Competition Commission, Government Procurement